Penyuluhan penanganan pasca panen kopi robusta pada kelompok tani kopi Desa Bocek, Kabupaten Malang - Rafaella Chandraseta Megananda; Endyana Siefani Puteri (Progran Studi Farmasi STIKES Mandala Waluya, 2022)
Post-harvest handling is one of the most important things in determining coffee quality. Bocek Village has the main commodity in the form of coffee, but the coffee harvest is often damaged due to poor post-harvest handling. There are two methods in post-harvest handling, namely the dry processing and wet processing. The right post-harvest handling method applied to farmer groups in Bocek Village is the dry method. Through this outreach activity, it is hoped that it can increase public knowledge about the dry method of processing coffee in order to produce coffee with good quality. Extension activities are carried out in three stages, namely preparation, counseling and evaluation. Based on the extension activities carried out, it showed that the farmer groups were actively involved in extension activities and received well the material presented. The dry method coffee handling process consists of several stages, namely sorting, drying, stripping, sorting dry beans, packaging and storage. Through the activities that have been carried out, it is hoped that it can increase public knowledge about post-harvest handling of coffee and can be applied to produce coffee with good quality.